Leadership the hard way why leadership can?t be taught and how you can learn it anyway - Frohman, Dov. (San Francisco Jossey-Bass, 2008)
Leadership the Hard Way presents a method of living and working that can truly facilitate the learning of leadership. Their method shows how to go against the current, fight conventional wisdom, and embrace the unexpected. It is about trusting oneself and valuing intuition, principles, and imagination as much as hard skills and analysis. Frohman combines his counterintuitive ideas with experiences from his own background?from escaping the Nazis as a child to becoming a leading innovator in the semiconductor industry?to show how readers can build their own leadership abilities. A leader?s values and personality, he ultimately reveals, are the only sure source of stability in a world of continuous change.
"A Warren Bennis book"--P. [v].
Keywords: Leadership